Dynamics of BMP and Hes1/Hairy1 signaling in the dorsal neural tube underlies the transition from neural crest to definitive roof plate. Issue 1 (December 2016) - Nitzan, Erez; Avraham, Oshri; Kahane, Nitza; Ofek, Shai; Kumar, Deepak; Kalcheim, Chaya
Abstract Background The dorsal midline region of the neural tube that results from closure of the neural folds is generally termed the roof plate (RP). However, this domain is highly dynamic and complex, and is first transiently inhabited by prospective neural crest (NC) cells that sequentially emigrate from the neuroepithelium. It only later becomes the definitive RP, the dorsal midline cells of the spinal cord. We previously showed that at the trunk level of the axis, prospective RP progenitors originate ventral to the premigratory NC and progressively reach the dorsal midline following NC emigration. However, the molecular mechanisms underlying the end of NC production and formation of the definitive RP remain virtually unknown. Results Based on distinctive cellular and molecular traits, we have defined an initial NC and a subsequent RP stage, allowing us to investigate the mechanisms responsible for the transition between the two phases. We demonstrate that in spite of the constant production of BMP4 in the dorsal tube at both stages, RP progenitors only transiently respond to the ligand and lose competence shortly before they arrive at their final location. In addition, exposure of dorsal tube cells at the NC stage to high levels of BMP signaling induces premature RP traits, such asHes1 /Hairy1, while concomitantly inhibiting NC production. Reciprocally, early inhibition of BMP signaling preventsHairy1 mRNA expression at the RP stage altogether, suggesting that BMP is both necessary and sufficient for the development of this RP-specific trait. Furthermore, when Hes1/Hairy1 is misexpressed at the NC stage, it inhibits BMP signaling and downregulatesBMPR1A/Alk3 mRNA expression, transcription of BMP targets such asFoxd3, cell-cycle progression, and NC emigration. Reciprocally, Foxd3 inhibitsHairy1, suggesting that repressive cross-interactions at the level of, and downstream from, BMP ensure the temporal separation between both lineages. Conclusions Together, our data suggest that BMP signaling is important both for NC and RP formation. Given that these two structures develop sequentially, we speculate that the longer exposure of RP progenitors to BMP compared with that of premigratory NC cells may be translated into a higher signaling level in the former. This induces changes in responsiveness to BMP, most likely by downregulating the expression of Alk3 receptors and, consequently, of BMP-dependent downstream transcription factors, which exhibit spatial complementary expression patterns and mutually repress each other to generate alternative fates. This molecular dynamic is likely to account for the transition between the NC and definitive RP stages and thus be responsible for the segregation between central and peripheral lineages during neural development.